Analisis Pengelolaan Dana Desa Dalam Pemberdayaan Masyarakat Menurut Perspektif Ekonomi Islam Di Desa Sengkati Baru Kecamatan Mersam Kabupaten Batang Hari - Rika Susanti; Arsa Arsa; Ahsan Putra Hafiz; Rohana (Universitas Kristen Indonesia Toraja, 2023)
This research was conducted to find out whether the new Sengki village government was economical, and to develop community economic empowerment infrastructure. This research method uses a qualitative method which originates from the Sengkatan Baru village office, sub-district. Mersam District. Batanghari. The results of the research conducted by the researchers concluded: 1. The planning stage of Village Fund Allocation in the village of Rambahan is in accordance with what was planned by the village government and in accordance with the needs of the community to improve the standard of living of the community. However, the lack of participation of the Sengkuti Baru village community in the deliberations on the Determination of the Use of the Village Fund Budget resulted in several parties having different opinions. 2. The implementation of the Village Fund Allocation (ADD) for the empowerment of rural communities is appropriate from an Islamic economic viewpoint, because it has applied the ta'awun principle and the shura principle quite well according to the Islamic perspective. 3. The use of the village fund budget in Seangkati Baru Village, Mersam District, can be seen from the success of the financial performance of village funds in Rambahan Village for 2019-2021 in the like category, based on the category and proportion of each statistical statement, the average is in the good category and the percentage above 60% until it reaches below 80% success.